I'm trying to find the general solution of $$\frac{\partial^2 u}{\partial xt}=6x+12t^{2}$$, where $u=u(x,t)$, subject to $u(x,2)=5$ and $u(1,t)=2t+1$.

My solution is as follows;

First integrating wrt $t$ gives $$\frac{\partial u}{\partial x}=\int(6x+12t^{2})dt=6xt+4t^{3}+f(x)$$ thus $$u(x,t)=3x^{2}t+4t^{3}x+f_{1}(x)+g(t)$$ Since we integrate $\frac{\partial u}{\partial x}$ with respect to $x$ this time, and $\int f(x)dx=f_{1}(x)+g(t)$ where $f(x),f_{1}(x),g(t)$ are arbitrary functions. I'm unsure how to apply the initial conditions from this step. I assumed that for the first condition I would just let $u(x,t)=5$ and substitute the value of $2$ in for t$ but then I still have those functions in the solution. I was wondering if anyone would be able to help clarify what I need to do and how to continue.

  • 2
    $\begingroup$ it should be $t^3x$ and not $t^3$ $\endgroup$ Apr 25, 2018 at 20:21
  • 1
    $\begingroup$ Ah thanks for that I think that was a typo will fix now $\endgroup$
    – Gibberish
    Apr 25, 2018 at 22:05
  • $\begingroup$ How would I apply the boundary conditions to find the general solution ? $\endgroup$
    – Gibberish
    Apr 26, 2018 at 16:27

1 Answer 1


$$u(x,t)=3x^{2}t+4t^{3}x+f(x)+g(t)\quad\text{is OK.}$$ First condition, $u(x,2)=5$ $$6x^{2}+32x+f(x)+g(2)=5$$ $$f(x)= -6x^{2}-32x+5-g(2)$$ $$u(x,t)=3x^{2}t+4t^{3}x-6x^{2}-32x+5-g(2)+g(t)$$ Second condition, $u(1,t)=2t+1$ $$3t+4t^{3}-6-32+5-g(2)+g(t)=2t+1$$ $$g(t)=2t+1-3t-4t^3+6+32-5+g(2)$$ $$g(t)= -4t^3-t+34+g(2)$$ $$u(x,t)=3x^{2}t+4t^{3}x-6x^{2}-32x+5-g(2)-4t^3-t+34$$ $$u(x,t)=3x^{2}t+4t^{3}x-6x^{2}-32x+5-g(2)-4t^3-t+34+g(2)$$ Solution : $$u(x,t)=3x^{2}t+4t^{3}x-6x^{2}-32x-4t^3-t+39$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.